ALPK1 Aggravates TMJOA Cartilage Degradation via NF-κB and ERK1/2 Signaling. (November 2022) - Liu, X.; Zhao, J.; Jiang, H.; Li, H.; Feng, Y.; Ke, J.; Long, X.
Temporomandibular joint osteoarthritis (TMJOA) is a common degenerative joint disease without effective intervention strategies. Previous research implied that alpha-kinase 1 (ALPK1) is involved in the inflammatory responses of gout, a chronic arthritis. Herein, we found the main distribution of ALPK1 in a proliferative layer of condylar cartilage and marrow cavity of subchondral bone, as well as a lining layer of synovial tissues in human temporomandibular joint. Moreover, the expression of ALPK1 was augmented in degraded condylar cartilage of monosodium iodoacetate (MIA)–induced TMJOA mice. After MIA induction, ALPK1 knockout mice exhibited attenuated damage of cartilage and subchondral bone, as well as synovitis, as compared with wide type mice. In contrast, intra-articular administration of recombinant human ALPK1 aggravated the pathology of MIA-induced TMJOA. Furthermore, ex vivo study demonstrated that ALPK1 exacerbated chondrocyte catabolism by upregulating matrix metalloproteinase 13 and cyclooxygenase 2 by activating NF-κB (nuclear factor–kappaB) signaling and suppressed anabolism by downregulating aggrecan by inhibiting ERK1/2 (extracellular signal–regulated kinase 1/2) in articular chondrocytes. Taken together, ALPK1 exacerbates the degradation of condylar cartilage during TMJOA through the NF-κB and ERK1/2 signaling pathway. This study provides a new insight regarding the role of ALPK1 during TMJOA pathology.